A capacitive micromachined ultrasonic transducer - Al-Khateeb, Khalid A. Saeed; Ismail, Sulastri; Uddin, Md. Jasim (2010)
A Capacitive Micro-machined Ultrasonic Transducer (cMUT) is presented. It is a new type of transducer that can be used to transmit and receive ultrasonic signals in medical scanners and a variety of other applications. The behavior of cMUT is investigated based on a proposed model of an equivalent circuit by which the characteristics are predicted. The simulation is carried out using microwave office simulator. The various elements of equivalent circuit and the signals produced by the cMUT are discussed and the results are shown in the following sections.